Fire Emergency Evacuation Simulation of a shopping mall using Fire Dynamic Simulator (FDS) (Journal of Chemical Engineering, 2017)
Fire accident in a shopping mall, garments factory and other labor intensive industries nowadays has become a common incident in Bangladesh and poses a great threat to life, facilities and economy of our country. In this work, fire and evacuation simulation was performed for a single stored shopping complex utilizing computational fluid dynamic techniques. Fire Dynamic Simulator with evacuation (FDS+Evac) software was used to simulate a shopping mall fire and study the effects of fire on the emergency egress process of people. The shopping mall of area 64 m2 comprises of seven rooms with a pool fire at the center of the mall is modeled for simulation. The total evacuation time (TET) for a fixed population density were estimated with the change of heat release rate, soot yield, soot density and the design pattern or geometry of shopping mall. The evacuation of agents in different time and different design pattern of the mall has been assessed using the data obtained from the simulation. FDS+Evac provides an integrating platform where the interaction between fire growth and evacuees can be taken into account by simultaneous simulation allowing a full coupling of the fire conditions and human behavior. This makes FDS is an effective tool for simulating large and high density crowds where the movement dynamics of evacuees is affected by the crowd pressure. Full scale fire experiment is often quite difficult to study the fine and crowds evacuation behavior. This paper illustrates a promising application of fire dynamic simulator (FDS+Evac) for fire and evacuation modeling to predict the total evacuation time.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 32-36